2014
DOI: 10.4172/2161-0495.1000177
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Accidental Chemical Poisoning Cases among Children (≤12 Years Old) Admitted to Hospital University Sains Malaysia: 5 Years Review

Abstract: Unintentional poisoning has been reported to commonly occur among children. Most of the poisoning cases were attributed to the household chemical products. Hence, a retrospective analysis of medical records of chemical poisoning cases among children ≤ 12 years had been carried out to profile the background, identifying the sources, determining the probability, determining the extent of the severity and the risk of chemical poisoning. Medical records of patients admitted from 2007 to 2011 were reviewed. Data wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…In a present study, boys are predominately more influenced than girls [62.6% versus 37.4%, 1.67:1]. This ratio was near that recorded in Malaysia [1.6:1] [9] , United Arab Emirates [1.35:1] [10] , Sri Lanka [1.29:1] [3] . Male kids are more active versus female and this nature is responsible for their higher poisoning incidences.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In a present study, boys are predominately more influenced than girls [62.6% versus 37.4%, 1.67:1]. This ratio was near that recorded in Malaysia [1.6:1] [9] , United Arab Emirates [1.35:1] [10] , Sri Lanka [1.29:1] [3] . Male kids are more active versus female and this nature is responsible for their higher poisoning incidences.…”
Section: Discussionsupporting
confidence: 53%
“…In the present study, poisoning material storage place was in the toilet [49.7%], bedroom [ [9] reported that most guardians left their youngsters solo without supervision when they were in the toilet, in 76% of cases harms were either effectively congenial or didn't have appropriate capacity place [26] . [27] .…”
Section: Discussionmentioning
confidence: 85%
“…[13] Accidental ingestion of poison is most common in children younger than two years of age because of their exploratory nature and the tendency to put everything in their mouth. [7,8] We report a case of acute poisoning from accidental ingestion of AlP in a 14-month-old girl. At presentation, the chemical agent contained in the poison was not known and her predominant features were those of excessive parasympathetic activities.…”
Section: Introdutionmentioning
confidence: 99%
“…The latter is more common in toddlers. [7][8][9][10] Many of these forms of poisoning from rodenticides/insecticides are often managed as organophosphate poisoning, an active ingredient commonly used in insecticides/pesticides.…”
Section: Introdutionmentioning
confidence: 99%
“…Household chemical product poisoning by accidental or intentional ingestion, injection or inhalation is the most commonly reported cases of poisoning in medical emergency departments (Kassiri et al, 2012;Adnan et al, 2013;Tangiisuran et al, 2017). Household chemical products, such as cleaning products and toiletries, are commonly used items and can be easily found in all homes all over the world.…”
Section: A Framework For Interpreting Knowledge Attitude and Practices In Poisoning Incidents Of Household Chemical Products Introductionmentioning
confidence: 99%